Research on Virtual Screening of Natural Compounds Against Protozoan Parasites Using Comparative Genomics and Molecular Docking Techniques - He, Menghan; Guo, Shuquan (International Journal of Public Health and Medical Research, 2024)
This study aims to identify conserved drug targets in protozoan parasites through genomic data mining and use computational virtual screening to discover small molecule inhibitors from the TCMSP database that target these conserved drug targets. Comparative genomics was applied to identify key drug targets in protozoan parasites, and high-throughput screening was conducted using the AutoDock Vina molecular docking program. The results were further refined using docking scores and the "ADME-Lipinski" rule, followed by an analysis of the interactions between small molecules and the drug targets. Potential small molecules with anti-parasitic activity were predicted. In this study, the DHFR-TS enzyme was identified as a conserved drug target for protozoan parasites through comparative genomics. Using DHFR-TS as the target and a known positive control ligand, six compounds with favorable drug-like properties were selected from the TCMSP database: MOL013376, MOL005018, MOL009591, MOL002047, MOL011499, and MOL012692. These compounds demonstrated superior binding affinity and interaction with DHFR-TS compared to the positive control ligand. This study combines comparative genomics and computational virtual screening to identify potential natural compounds from Traditional Chinese Medicine for protozoan parasites, providing a solid theoretical foundation for the design and experimental synthesis of novel anti-parasitic drug candidates.